The Influence of Self-Awareness on Individual Performance (The International Journal for Scientific Research, 2023)
In the fast-moving and tough world markets, regular business resources like money, workforce, and technology are insufficient for a company to win. This paper posits that good leadership from leaders, especially knowing themselves, is very important for the success of any company. Knowing yourself, which means understanding your personality and feelings from inside you, is studied. It's a big factor in how well leaders perform independently or in workplaces. This study examines how awareness of oneself is a big factor in leadership. It uses studies that describe and explain that self-awareness affects performance more than any other skill found in leaders. It talks about how knowing yourself, part of emotional intelligence, helps control your feelings and understand others. This affects your choices, the bonds you build with people, and finally, how well you are as a leader doing things. The study results aim to provide a new understanding of how self-awareness is essential in leadership.
Keywords: Self-awareness; Individual Performance; Leadership